IMPLICIT LANGUAGE APTITUDE: CONCEPTUALIZING THE CONSTRUCT, VALIDATING THE MEASURES, AND EXAMINING THE EVIDENCE: INTRODUCTION TO THE SPECIAL ISSUE. Issue 3 (July 2021) - Unknown
Abstract: This article discusses the conceptualization, measurement, and validity of a recently emerged construct in the field of second language acquisition (SLA)—implicit language aptitude (alternatively "implicit aptitude"). Implicit aptitude is a set of cognitive abilities that enable learners to make unconscious computations of the distributional and transitional probabilities of linguistic input. Implicit aptitude is key to an accurate understanding of the cognitive foundation of language learning and contributes significantly to the advancement of SLA theory and pedagogy. The article starts by clarifying the concept and components of implicit aptitude, elaborating its role in SLA theories, identifying its attributes, and discussing its measurement. It then synthesizes the empirical evidence on its divergent, convergent, and predictive validity, which refers to whether it is distinct or separable from explicit aptitude, whether measures of implicit aptitude are correlated, and whether it is predictive of learning outcomes, respectively. Next, the article provides an overview of the seven empirical studies included in this special issue that examined implicit aptitude from various perspectives. The article concludes by identifying future directions.